« Débarrasser la société de femme[s] de ce genre-là ». Appréhender les archives judiciaires au prisme du genre pour enquêter sur les féminicides - Margot Giacinti (Glad!)
This article focuses on cases of femicides in 19th century court records. Although femicide, in its contemporary understanding in France, seems to be reduced to its marital dimension (murder of a wife by her husband), the study of femicide archives based on Radford and Russell’s definition (1992) makes it possible to account for the diversity of cases of women killed by men and to identify the determining gender factors in the crime. Thus, the paper examines what might have prevented such a reading by looking at the practices of the actors involved in the judicial investigation, and by studying three — at first sight very different — cases in which the victim is a woman. The article concludes that there are recurrent factors that lead men to kill women, which demonstrate the exercise of male domination, and which allow the cases presented to be subsumed under the unitary category of femicide.